Figurative Language Used in September Event 2018 - Apple and Apple Event - September 7 - Sihar Gilbert Marcelino Sitompul; Herwindy Maria Tedjaatmadja (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study investigates how Apple Inc. used metaphorical language in two of its product presentation videos. "September 2018 - Apple" and "Apple Event - September 7" are the videos that have been studied. They include both live and pre-recorded presentations. The present study employs Harris's (2018) theoretical framework to identify the many forms of figurative language used in the two videos. These forms include simile, analogy, metaphor, catachresis, metonymy, synecdoche, personification, allusion, eponym, apostrophe, and transferred epithet. Video transcripts were examined using a qualitative methodology to find instances of metaphorical language. These results highlight various figurative language kinds and show variations in figurative language use between live and pre-recorded presentations. The findings reveal the insights of the figurative language usage in September Event 2018 - Apple and Apple Event - September 7. This study also found that the types of figurative language used in September Event 2018 - Apple and Apple Event - September 7 depends on the where and what format the presentation is set. It is also found that not all figurative language types are used in these two videos. There are some similarities where some figurative language is not being used in both videos, namely catachresis, allusion, eponym, apostrophe, and transferred epithet. Also, there are some differences where some types cannot be found in one of the videos, namely simile, analogy, metaphor, metonymy, synecdoche, and personification. It is suggested that this study needs an improvement for other electronic brands that also use product presentation for the launch of the new product.